Factors that influence the quality of work life in nursing departments: A management perspective - Cornelle Young; Janetta H. Roos (Elsevier, 2024)
Purpose: To explore factors that influence the quality of work life (QWL) as perceived by Heads of Nursing Departments (HoDs) at South African universities. Background: Quality of life includes work life as an important subdivision. Quality of work life has sequalae of (and, in turn, influences) other aspects of a person's life. By addressing factors that influence the QWL in nursing departments, nursing students are potentially provided with quality teaching and learning experiences.Nursing HoDs have an intimate and extensive knowledge of the current QWL at their universities. Their experience and knowledge contribute to the understanding of faculty, provincial, governmental and professional body processes on aspects which might influence the prevailing QWL in nursing departments. These processes include budgeting and managing work processes. Design and methods: A qualitative, descriptive research design was employed with data generated by in-depth interviews. Thematic analysis was performed on the transcribed data, first by familiarisation and immersion, followed by the development of codes, generation and revision of the final themes of the HODs' understanding of QWL regarding their personal, home and family situations, departmental (work) situations, finances, and the effect of #FeesMustFall. Results: HoDs indicate that the relationships with, and the amount of support received from different parties involved with teaching and student learning, as well as home, family and work-related issues, availability of finances and the drive for transformation in higher education facilitate the QWL in the department. Conclusion: To improve the QWL in nursing departments towards higher education transformation, nursing departments need good human resources (HR) management practices.